If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(4w + 3) * 3 = -11 Reorder the terms: 4(3 + 4w) * 3 = -11 Reorder the terms for easier multiplication: 4 * 3(3 + 4w) = -11 Multiply 4 * 3 12(3 + 4w) = -11 (3 * 12 + 4w * 12) = -11 (36 + 48w) = -11 Solving 36 + 48w = -11 Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 48w = -11 + -36 Combine like terms: 36 + -36 = 0 0 + 48w = -11 + -36 48w = -11 + -36 Combine like terms: -11 + -36 = -47 48w = -47 Divide each side by '48'. w = -0.9791666667 Simplifying w = -0.9791666667
| C=5/2k-37 | | (-7x+13)(-x-8)=0 | | 5(2x+3)-6(-2x+1)=9(x-2) | | 2[x-2(x-1)]-3(3y-5)=-11 | | (2x-5)2-(x+1)2=7x | | -5(2t+2)=20 | | n+(-12)=3n | | X-2x+3=4x+2 | | 9x-9=9-8x | | 8x-16-2x=34 | | 12ab-28bc+20ac=0 | | x^(2/#)=1/3 | | 10x=0.000001 | | 3t^2-16t+21=0 | | -2x-6y+11=-11 | | 4n+21=-3 | | q^2+75q-6250=p | | q^2+75q-6250=q | | 4n^2-x-2000=0 | | 2x^2+6x-77=0 | | -3=6-x/9=3 | | -16times-0.15=x | | 6b(2a-3c)-5d(2a-3c)=0 | | 6(3s+6)=216 | | X-17=x+51 | | 3(x+10)=(2x+30) | | -16x-0.15=f | | 4(2l+5)=92 | | q^2+75q-6250=0 | | 0.51(2x)=x+1 | | (2x-1)(3x-1)=(6x+2)(x-4) | | 2x-9/5=x+18 |